Who benefits from return migration to developing countries? - Jackline Wahba (IZA World of Labor, 2021)
Return migration can have multiple benefits. It allows migrants who have accumulated savings abroad to ease credit constraints at home and set up a business. Also, emigrants from low- and middle-income countries who have invested in their human capital may earn higher wages when they return. However, whether the home country benefits from return migrants depends on the migrant's success in accumulating savings and human capital and on the home country's ability to make use of returnees' skills and investment. To benefit from returnees, home countries need policies that encourage returnees' investment and labor market reintegration.
Keywords: J61; O15; 330; return migration; entrepreneurship; brain gain; developing countries